Cranial Nerve Palsies as Initial Presentation of Acute Lymphoblastic Leukemia – A Case Report: Doi: 10.36351/pjo.v39i3.1635 - Ghoauri, Muhammad Sohail Ajmal; Butt, Nauman Ismat; Dur-e-Sabeeh; Rasheed, Muhammad Bilal; Javed, Muhammad Umair (Pakistan Journal of Ophthalmology, 2023)
The clinical manifestations of acute leukemia are diverse and can range from asymptomatic to life-threatening Complications.1 Cranial nerve palsies as a presenting feature of this disease is relatively rare. It can be attributed to leukemic infiltration of cranial nerves, or the development of cranial nerve palsies secondary to intracranial complications such as subdural hematoma. Our patient presented with 4-month history of progressively worsening eye and visual disturbances. On examination, there was bilateral ptosis and proptosis. The right pupil was dilated and non-responsive to light with complete blindness. Left pupil had a sluggish response to light and had decreased visual acuity. There was 6th nerve palsy on left side and bilateral sensorineural hearing loss. Bone marrow biopsy showed Acute Lymphoblastic Leukemia. He was diagnosed with Acute Lymphoblastic Leukemia with brain (CNS) infiltration causing 2nd, 3rd, 6th and 8th cranial nerve palsies.